A dimensão do toque na experimentação: uma investigação de espaços de hesitação no design - Maccagnan, Ana Maria Copetti (Universidade do Vale do Rio dos Sinos, 2021)
Uncertainty is one of the most prominent features of existence. However, society has great difficulties in dealing with it, always looking for solutions that would reduce it to manageable programs. Strategic design being what concerns actions along with strategy, it must turn to processes that allow experimenting with new ways of being, doing, thinking and feeling. This includes opening up to other modes of attention related to the condition of hesitation in the construction of a common and detached world. In other words, a deceleration is essential to stop general solutions to be implemented before one can have the opportunity to question what is good or urgent. This investigation addressed the role of experimenting within the design processes, by proposing an understanding of an experimental posture intertwined with the dimension of touch. Being touch, a sensorial experience capable of achieving particular knowledge generated in contact. In this experimentation bias, the material aspect of the inventive dynamics of design is valued, which, by means of collective and participatory practices of doing, mediate expectations and worldviews which defies what is established as true. Thus, the purpose of this work is to research how experimentations and touch favour the creation of spaces of hesitation in design and do so by outlining a methodological approach that aims to identify the potential of experimental prototyping practices carried out through embroidery. To do so, the action-research method was used, organized in cycles of experimentation structured around the free creation and imagination of a group of six people through the medium of hand embroidery. Based on what emerged from the practice, the findings are discussed as the capacity to promote oscillating between experimentation and programming, a rhythm variation, an ethos of care and an experimental prototyping that generates narratives. Such reflections guide the design to new understandings of experimentation as a process that allows to hesitate when accessing other sensitivities and affections.
Keywords: Experimentação; Toque; Espaços de hesitação; Prototipagem experimental; Design estratégico; Experimentation; Touch; Hesitation spaces; Hesitation spaces; Experimental prototyping; Strategic design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial